Peran Guru Bimbingan dan Konseling Dalam Meningkatkan Minat Melanjutkan Studi ke Perguruan Tinggi - Nisa, Afiatin (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this research is to know the role of teacher guidance and counseling in increasing interest to continue study to university at student at SMK Nurul Hikmah Bekasi. The research method used by the researcher is qualitative method with descriptive approach, that is by spreading the questionnaire, observation, and interview with what is from a symptom of phenomenon that exist when research done data and data source in this research is teacher guidance and counseling and student of SMK Nurul Hikmah Bekasi. The research instrument used in this research is questionnaire, interview, observation and documentation. Survey and observation result data after check and recheck the validity of the data then described what it is. After analyzing the researchers, it can be concluded that the role of teacher guidance and counseling in providing services to foster interest to continue studies to college students in SMK Nurul Hikmah done optimallyThe purpose of this research is to know the role of teacher guidance and counseling in increasing interest to continue study to university at student at SMK Nurul Hikmah Bekasi. The research method used by the researcher is qualitative method with descriptive approach, that is by spreading the questionnaire, observation, and interview with what is from a symptom of phenomenon that exist when research done data and data source in this research is teacher guidance and counseling and student of SMK Nurul Hikmah Bekasi. The research instrument used in this research is questionnaire, interview, observation and documentation. Survey and observation result data after check and recheck the validity of the data then described what it is. After analyzing the researchers, it can be concluded that the role of teacher guidance and counseling in providing services to foster interest to continue studies to college students in SMK Nurul Hikmah done optimally